The challenges of prenatal care for Bangladeshi women: a qualitative study. (3rd September 2018) - Akter, M.K.; Yimyam, S.; Chareonsanti, J.; Tiansawad, S.
Abstract : Background: Maternal and infant morbidity and mortality are major issues in developing countries, but the literature reveals there are limited studies on the sociocultural issues affecting adequate prenatal care in Bangladesh. Aim: To explore the sociocultural influences underlying perceived barriers to prenatal care among pregnant women in an urban area of Bangladesh. Methods: A descriptive qualitative research was conducted with 20 women and 20 of their significant others in three purposively sampled hospitals using individual in‐depth interview between November 2016 and March 2017. Content analysis was used for analysis. Findings: Six themes emerged as follows: women's lack of opportunity to make decision; pregnancy as a normal life event; insufficient money for prenatal care; heavy family workload without family support; no permission to go to hospital without a guardian; and inconvenient transportation. Discussion: Good prenatal care is vital for maternal and infant health, but our participants were challenged by a number of key issues as follows: they lacked empowerment to make their own pregnancy decisions, they were impoverished financially, struggled to get to their prenatal appointments by local transport and they lacked family understanding and support for necessary prenatal care. Conclusion and policy implications: Based on the findings, it is recommended that promoting prenatal care adequacy among pregnant women in Bangladesh needs socioculturally sensitive health education programmes which target are not only pregnant women, but also their significant others who are authorized persons in the family. It should be established remote PNC services. Empowerment of women is vital in the country and free antenatal education programmes are needed through a variety of media. Findings provide information for nursing and health policymakers to develop policies to improve adequacy of prenatal care among pregnant women.